WHEAT FLOUR PRESERVATION BY MEANS OF PACKAGING AND ITS STATISTICAL EVALUATION - Khan, A D; Ejaz, Nusrat; Abdullah, Naheed; Javed, Akmal (Biological Sciences - PJSIR, 2002)
The wheat flour (atta) stored in conventional packaging materials i.e. jute (gunny), cloth, woven polyethylene threads bags which were in contact with air deteriorated more quickly than the wheat flour stored in air tight polyethylene acetate bags containing free oxygen absorber (FOA). The colour, taste , texture, flavour , acidity, organoleptic evalation, insect and bacterial count remained acceptable for two months in polyethylene -acetate coated impermeable bags containi ng FOA and insect infestation was zero. These changes were due to anaerobic fermentation of starch in wheat flour. The statistical presentation of the data has been carried out.